International Deployment of Visual IoT for Disaster Mitigation - Ken T. Murata; Kazutaka Kikuta; Tsutomu Nagatsuma; Hideo Imanaka; Praphan Pavarangkoon (My University, 2023)
This paper proposes a novel methodology that utilizes a newly developed visual Internet of Things (IoT) system for resilient natural disaster mitigation. This system enables the detection of disasters through remote control functions integrated with visual IoT sensors and artificial intelligence (AI)-based image processing of images captured by these sensors. The system is designed using commercial off-the-shelf (COTS) components to reduce installation costs, making it feasible for deployment worldwide, including in developing countries. In 2023, the proposal for this system was presented to the ITUD with the aim of widespread implementation in developing nations. The paper introduces innovative methodologies for visual IoT in international disaster mitigation, accompanied by use cases and detailed technological insights.
Keywords: COVID-19 diagnosis using AI; IoT and Edge/Fog Computing; IoT-based Smart Home Systems